School Environmental Intervention to Reduce Particulate Pollutant Exposures for Children with Asthma - Jhun, Iny (J Allergy Clin Immunol Pract, 2016)
BACKGROUND: Home-based interventions to improve indoor air quality have demonstrated benefits for asthma morbidity, yet little is known about the effect of environmental interventions in the school setting. OBJECTIVE: We piloted the feasibility and effectiveness of a classroom-based air cleaner intervention to reduce particulate pollutants in classrooms of children with asthma. METHODS: In this pilot randomized controlled trial, we assessed the effect of air cleaners on indoor air particulate pollutant concentrations in 18 classrooms (9 control, 9 intervention) in 3 urban elementary schools. We enrolled 25 asthmatic children (13 control, 12 intervention) aged 6–10 years old. Classroom air pollutant measurements and spirometry were completed once prior to and twice after randomization. Asthma symptoms were surveyed every 3 months. RESULTS: Baseline classroom levels of fine particulate matter (PM(2.5)) and black carbon (BC) were 6.3 μg/m(3) and 0.41 μg/m(3), respectively. When comparing the intervention to the control group, classroom PM(2.5) levels were reduced by 49% and 42%, and BC levels were reduced by 58% and 55% in the first and second follow-up periods, respectively (p < 0.05 for all comparisons). When comparing the children randomized to intervention and control classrooms, there was a modest improvement in peak flow, but no significant changes in forced expiratory volume in 1 second (FEV1) and asthma symptoms. CONCLUSION: In this pilot study, a classroom-based air cleaner intervention led to significant reductions in PM(2.5) and BC. Future large-scale studies should comprehensively evaluate the effect of school-based environmental interventions on pediatric asthma morbidity.